Surgical Treatment of Posttraumatic Ophthalmoplegia Through the Reconstruction of the Lateral Orbital Wall - Sales, Pedro Henrique Da Hora; Rocha, Suellen Sombra Da; Rodrigues, Paulo Henrique Carvalho; Cetira Filho, Edson Luiz; Silva, Leonardo De Freitas [UNESP]; Mello, Manoel De Jesus Rodrigues (Wolters Kluwer, 2017)
Orbital fractures are injuries frequently related to traumas of the midface. These fractures can be associated with ocular lesions, ranging from small abrasions on the cornea to serious complications such as hyphema and ocular globe rupture. Diplopia and ophthalmoplegia are common findings in orbital fractures. They can be caused by mechanical factors as bone fragments or muscle imprisonment. The aim of this study was to report a case of a 40-year patient, male showing diplopia and ophthalmoplegia due to the orbital fracture. The patient was treated by general anesthesia. It was performed a supra orbital approach and the fragments were removed. A titanium mesh to restore the orbital anatomy was installed. After 40 days of follow-up, the patient has no aesthetic or functional complaints. In orbital traumas, the ophthalmological evaluation should be performed carefully aiming to avoid ocular sequelaes. In surgical patients, the surgery should be done as early as the clinical conditions permit, to restore the ocular function.
Keywords: Diplopia; ophthalmoplegia; orbital fractures